Phytochemicals present in the different parts of the Malunggay plant (Moringa oleifera) - Macoycruz, Rubilee A. (Universidad de Zamboanga Journal : Official Peer Reviewed Journal Publication, 2014)
This study was done primarily to determine the phytochemicals present in the different parts of the Malunggay plant (Moringaoleifera). This is a qualitative chemical investigation of the phytochemical content of the ethanolic extract from the Malunggay seeds, flowers, leaves, bark and roots. He experimental procedure involves the preparation and air-drying of the samples, extraction, and finally screening of the presence of the following substances: anthraquinone, tannins and phenolic compounds, saponins, alkaloids, deoxysugars, unsaturated sterols and striterpenes, flavonoids, and leucoanthocyanins. The result of the screening tests conducted on the extract reveals that the Malunggay seeds' extract contains anthraquinone, saponins, alkaloids, tannins and phenolic compounds, unsaturated sterols and striterpenes, flavonoids and leucoanthocyanins. Flowers contain anthraquinone, alkaloids, tannins and phenolic compounds, unsaturated sterols and striterpenes, flavonoids and leucoanthocyanins. The leaves contain alkaloids, tannins and phenolic compounds, deoxysugars, unsaturated sterols and striterpenes, flavonoids and leucoanthocyanins. The bark contains saponins, alkaloids, tannins and phenolic compounds, unsaturated sterols and striterpenes, flavonoids and leucoanthocyanins. Roots contain alkaloids, tannins and phenolic compounds, unsaturated sterols and striterpenes, flavonoids and leucoanthocyanins.